2005
DOI: 10.1007/s10562-005-6498-2
|View full text |Cite
|
Sign up to set email alerts
|

An FT-IR Study of NO2 Reduction in Nanocrystalline NaY Zeolite: Effect of Zeolite Crystal Size and Adsorbed Water

Abstract: In this study, in situ transmission FT-IR spectroscopy was employed to investigate the selective catalytic reduction (SCR) of NO 2 in nanocrystalline NaY zeolite with a crystal size of 23 nm. Two specific aspects of this reaction were explored in this study: the importance of zeolite crystal size and the effect of water on the propylene-SCR reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 46 publications
4
54
0
Order By: Relevance
“…IR spectra of ODA mainly showed N-H bending vibration (3332 cm −1 ), C-H stretching vibration (2849 and 2917 cm −1 ), as well as H-C-H and H-N-H bending vibrations (region 1300-1700 cm −1 ) [11] . These ODA characteristic bands were hardly distinguished from the IR spectra of amphiphilic 5% ODA/HY zeolite, instead three new bands, which were attributed to ODA adsorbed on Lewis acidic sites and Brønsted acidic sites, appeared at 1462, 1520, 1612 cm −1 [12] , and water absorption band appeared at 1632 cm −1 [13] . At the same time, intensity of the hydroxyl groups on parent zeolite was decreased.…”
Section: Resultsmentioning
confidence: 93%
“…IR spectra of ODA mainly showed N-H bending vibration (3332 cm −1 ), C-H stretching vibration (2849 and 2917 cm −1 ), as well as H-C-H and H-N-H bending vibrations (region 1300-1700 cm −1 ) [11] . These ODA characteristic bands were hardly distinguished from the IR spectra of amphiphilic 5% ODA/HY zeolite, instead three new bands, which were attributed to ODA adsorbed on Lewis acidic sites and Brønsted acidic sites, appeared at 1462, 1520, 1612 cm −1 [12] , and water absorption band appeared at 1632 cm −1 [13] . At the same time, intensity of the hydroxyl groups on parent zeolite was decreased.…”
Section: Resultsmentioning
confidence: 93%
“…Comparing with the HZSM-5(N), the HZSM-5(M) had significant larger absorption band at 3600 cm )1 due to Bro¨nsted acid hydroxyl groups [17,18]. For the two zeolites, same scale of IR absorption in intensity of the bands both at 3737 cm )1 due to terminal silanol groups and at 3665 cm )1 due to hydroxyl groups attached to extra framework alumina [19] were observed. The results indicated that the zeolites had about same amount of the two kinds of hydroxyl groups.…”
Section: Activity Evaluationmentioning
confidence: 83%
“…This was assigned to bridging hydroxyls projecting into the supercage [20]. The hydroxyls responsible were found to be very acidic, which was interpreted in terms of an interaction with neighbouring extra-framework Al atoms [21]. The narrow band towards 3565 cm -1 observed in the PdNaY700 spectra indicates absorption of bridged acidic hydroxyl groups (Al-Si-OH) situated in the hexagonal prisms of the zeolite.…”
Section: Characterisationmentioning
confidence: 90%